Synergy between antiangiogenic and immuno-therapies in breast cancer - Ferreira, Daniela Pais (2015)
Angiogenesis is crucial for breast cancer growth, progression and dissemination, making it a promising therapeutic target. Given the dominant role of Vascular Endothelial Growth Factor (VEGF) signaling in tumor angiogenesis, the majority of clinical studies with anti-angiogenic therapies in breast cancer were based on VEGF blockade. However, lack of clinical efficacy was observed in all clinical studies with antiangiogenic therapies for breast cancer. Since angiopoietin 2 (ANG-2) has been reported to induce therapeutic resistance after VEGF-targeted therapies, breast cancer patients may benefit from a therapeutic strategy that simultaneously blocks ANG-2 and VEGF-A. Indeed, using the bispecific ANG-2/VEGF-A targeting antibody (A2V), durable inhibition of tumor progression, as well as increased survival, could be observed after dual ANG-2/VEGF-A blockade in the aggressive mouse model of breast cancer, the MMTV-PyMT transgenic mouse. Consistent with tumor inhibition, increased tumor necrosis and a drastic reduction of vascular density was observed after A2V therapy, with little evidence of tumor revascularization or resistance to therapy. Moreover, A2V led to increased perivascular coverage of the remaining tumor blood vessels, favoring vascular normalization, which is known to facilitate the development of an immunosupportive microenvironment. These findings suggested that breast cancer immunotherapy may benefit from the combination with A2V. Therefore the A2V mAb was combined with a CD40 agonistic antibody (FGK45). The combined therapeutic approach led to remarkable tumor growth inhibition in an orthotopic MMTV-PyMT model, with the achievement of cases of stable disease and further increase in tumor necrosis. Increased infiltration of CD8+ cells after FGK45 therapy, either alone or in combination with A2V, could also be observed. Of note, a correlation between the extent of tumor inhibition and increased tumor infiltration by CD8+ cells was detected, suggesting that the influx of CD8+ cells in the combination therapy-treated tumors was responsible for the remarkable anti-tumor responses observed. In summary, these results point to a significant synergistic activity of anti-ANG-2/VEGF-A and CD40 agonistic therapy in the MMTV-PyMT model of breast carcinoma. This combinatorial approach may benefit breast cancer patients, so further studies that explore the mechanistic bases of the cooperative activity of antiangiogenic and immunostimulatory therapy are warranted.